Hazards analysis : reducing the impact of disasters - Pine, John C., 1946- (CRC Press, 2014)
"The impacts of natural and manmade disasters have been increasing at exponential rates over the past few decades. Our global interconnectedness and the scale of disaster events has grown to the point where catastrophic disasters have regional, national, and even global economic consequences. This volume presents a systematic process of hazards identification, vulnerability determination, and consequence assessment for the natural, built, and human environment. The book aims to examine strategies that may be taken at the individual, organization, community, and regional levels to reduce the adverse consequences of disasters and to foster sustainability." Provided by publisher.
Keywords: Disasters -- Social aspects.; Emergency management.; Preparedness.; Community organization.; Disasters -- Risk assessment.; Risk management.; elektronické knihy; electronic books